Kegiatan Belajar Terganggu karena Banyak Menggunakan Handphone: Studi Kasus pada Siswa MAN 2 Model Medan dan Cara Penanganannya oleh Guru BK - Harahap, Ade Chita Putri; Rambe, Afghan Bai Asy Ary; Azzura, Aika; Ashari, Ayu; Al Mefa, Fadira; Rahmayani, Hafsah Dahni; Rezky, Sri; Atari, Nabila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find out whether the use of mobile phones can disrupt students' learning activities and to determine the handling usually given by guidance and counseling teachers. The research method used in this study is a descriptive qualitative research method using data collection techniques, namely interviews and observations. The research subjects in this study are guidance and counseling teachers at MAN 2 Medan and 21 students at MAN 2 Medan. The results show that the use of mobile phones can disrupt students' learning activities but on the other hand, the teaching and learning process at MAN 2 Model is also somewhat assisted by technology in the form of mobile phones, such as providing materials, google forms, and instructional videos in certain subjects. The handling provided by guidance and counseling teachers is to provide information services for mild cases and for severe cases, guidance and counseling teachers will call the parents of the students.